Calebin A modulates inflammatory and autophagy signals for the prevention and treatment of osteoarthritis - Brockmueller, Aranka; Buhrmann, Constanze; Shayan, Parviz; Shakibaei, Mehdi (Frontiers in Immunology, 2024)
Background and objectives: Osteoarthritis (OA) is associated with excessive cartilage degradation, inflammation and decreased autophagy. Insufficient efficacy of conventional monotherapies and poor tissue regeneration due to side effects are just some of the unresolved issues. Our previous research has shown that Calebin A (CA), a component of turmeric (Curcuma longa), has pronounced antiinflammatory and anti-oxidative effects by modulating various cell signaling pathways. Whether CA protects chondrocytes from degradation and apoptosis in the OA environment (EN), particularly via the autophagy signaling pathway, is however completely unclear.: To study the anti-degradative and anti-apoptotic effects of CA in an inflamed joint, an in vitro model of OA-EN was created and treated with antisense oligonucleotides targeting NF-B (ASO-NF-B), and IB kinase (IKK) inhibitor (BMS-345541) or the autophagy inhibitor 3methyladenine (3-MA) and/or CA to affect chondrocyte proliferation, degradation, apoptosis and autophagy. The mechanisms underlying the CA effects were investigated by MTT assays, immunofluorescence, transmission electron microscopy and Western blot analysis in a 3D-OA highdensity culture model.In contrast to OA-EN or TNF-α-EN, a treatment with CA protects chondrocytes from stressinduced defects by inhibiting apoptosis, matrix degradation as well as signaling pathways associated with inflammation (NF-B, MMP9) or autophagy-repression (mTOR/PI3K/Akt), while promoting the expression of matrix compounds (collagen II, cartilage specific proteoglycans), transcription factor Sox9 and autophagy-associated proteins (Beclin-1, LC3). However, the preventive properties of CA in OA-EN could be partially abrogated by the autophagy inhibitor 3-MA.The present results reveal for the first time that CA is able to ameliorate the progression of OA by modulating restoring impaired autophagy pathway, inhibiting inflammation and apoptosis in chondrocytes, suggesting that CA may be a novel therapeutic compound for OA.